SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/95430-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effective Torque Management of Wytch Farm Extended-Reach Sidetrack Wells

Abstract: Wytch Farm was at the forefront of extended-reach drilling (ERD) during the 1990's. This was achieved through opportunity, innovation, technology and team work. Late life management of the field has now required that cost-effective sidetrack wells be drilled to sweep the remaining oil in place in the offshore part of the field. As with many ERD developments, one specific challenge associated with the original Wytch Farm wells was the ability to control torque and drag within manageable levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…One possible explanation for this reduction is that fiber particles have a tendency to act as roller bearings when the drillstring rotates or moves axially in and out of the wellbore. Field experiments (Robertson et al 2005) that were conducted using fibrous LCM showed reduction of the wellbore friction factor from 0.31 to 0.21. In addition, the presence of the LCM in the wellbore-fluid system greatly reduced stick/slip phenomena.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this reduction is that fiber particles have a tendency to act as roller bearings when the drillstring rotates or moves axially in and out of the wellbore. Field experiments (Robertson et al 2005) that were conducted using fibrous LCM showed reduction of the wellbore friction factor from 0.31 to 0.21. In addition, the presence of the LCM in the wellbore-fluid system greatly reduced stick/slip phenomena.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One specific challenge associated during drilling of ERD wells is the ability to control torque and drag within manageable levels. The study conducted by Robertson et al (2005) indicated that the addition of certain LCMs has a profound impact on torque and drag. The mechanism by which the LCM reduces the torque and drag is believed to be a combination of better hole cleaning and increased lubricity.…”
Section: Literature Reviewmentioning
confidence: 99%